Effects of isolated and combined ingestion of sodium bicarbonate and ß-alanine on combat sports athletes' performance: a systematic review - Lopes-Silva, J. P.; Franchini, E. (Strength and Conditioning Journal, 2021)
This systematic review analyzed the isolated and combined effects of sodium bicarbonate (NaHCO3) and beta-alanine (ß-alanine) supplementation on combat sports athletes' performance. Using the PRISMA guidelines, studies were identified through 3 databases and only 10 articles were included, 6 investigated the isolated ingestion of NaHCO3, 3 investigated isolated ingestion of ß-alanine, whereas only 1 investigated the coingestion of NaHCO3 and ß-alanine on combat sports performance. The results showed that both acute isolated ingestion and chronic isolated ingestion of NaHCO3 and chronic ß-alanine are effective to improve combat sports athletes' performance and the coingestion of ß-alanine and NaHCO3 resulted in additional improvements.